Review of Iain Borden, Skateboarding and the City: A Complete History (London and New York, NY: Bloomsbury, 2019) - Alexandros Daniilidis (Janeway JS, 2020)
This is a review of Iain Borden's latest publication on skateboarding and its attributes as a spatial practice.